An economic valuation of Marikina City library using revealed preference methods - Obal, Manilyn R.; Dorado, Dan Anthony D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
To address the increasing demand for public libraries to redefine their values and justify their existence in this Digital Age, this study focused on one of the public libraries in the Philippines, Marikina City Library (MCL) and the estimation of its Total Economic Value (TEV) - the sum of the use and non-use benefits, expressed in monetary terms, that a person or a group of person could get from the direct, indirect use or non-usage of certain goods or services. TEV of MCL was estimated using an economic-value measurement model that was adapted based on Revealed Preference Theory, which asserts that a person's preferences can be deduced from his or her behavior and actual choices.
Data collection of the actual choices of MCL visitors and donors who are Marikina residents like borrowing and donating books were identified using two (2) research instruments: (1) MCL records and, (2) structured moderate participant observation-an observation done in a natural setting with the researcher acting as a participant. These observed choices were then quantified using the economic-value measurement model which was a combination of market analogy and actual donations.
The economic-value measurement process resulted to a total of P 21,824, 703.81 TEV. Relative to the public fund of MCL for the year 2014 that amounts to P4, 244,797.96, the computed TEV in this study implies that for every P1.00 of investment in MCL, Marikina residents and Marikina City get a total of P5.14 in return. This result proves that it is worth it to invest in a public library like MCL.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Valuation -- Philippines -- Marikina City; Public libraries -- Philippines -- Marikina City